The effect of nitrogen on the microbiological and biochemical properties of zinc-contaminated soil - Strachel, Rafał; Wyszkowska, Jadwiga; Baćmaga, Małgorzata (Journal of Environmental Engineering and Landscape Management, 2017)
The aim of  these studies was to determine the influence of excessive zinc doses on the microbiological and enzymatic properties of soil. Also, an evaluation of the possibility to stimulate remediation processes by nitrogen fertilisation of the soil was attempted. Zinc was applied to loamy sand in the amounts of 0, 250, 500, 750, 1000, 1250 mg Zn2+ kg–1 DM soil, while nitrogen in the form of urea in doses of 0, 250, 500 mg N kg–1 DM soil. Soil samples were incubated at a temperature of 25 °C, maintaining a constant humidity equal to 50% of the maximum water capacity. In the 2nd and 20th week of the experiment, the following factors were determined: activity of dehydrogenases and catalase, and number of organotrophic bacteria, copiotrophic bacteria, oligotrophic bacteria, actinomycetes, and fungi. Zinc inhibited the enzymatic activity of the soil, while causing a slight increase in populations of microorganisms. Only fungi reacted unequivocally positively to contamination of the soil with zinc, therefore demonstrating changes in the biodiversity of microorganisms. Nitrogen fertilisation of the soil resulted in stabilization of the environment contaminated with zinc by stimulation of growth of microorganisms resistant to the influence of this metal.